ESTUDO DE CASO DE PACIENTE ONCOLÓGICO TERMINAL: UM RELATO DE EXPERIENCIA - Bagetti, Taisa; Grimm, Julia Y.; Subutzki, Jordana P.; Martins, Graciele L.; Rosanelli, Cleci L. S. P.; Klein, Rubia N. (Salão do Conhecimento, 2013)
Resumo